Collective Memories of Everyday Life on the Isolated Island of Žirje in the Times of Socialism - Filip Škiljan; Ivana Škiljan; Natasha Kathleen Ružić (Svetovi, 2025)
This paper examines interview data exploring the collective memory of thirteen residents on the island of Žirje, focusing on life during communism. Oral histories describing collective memories are important sources of information especially in instances where archival records are either non-existent or very sparse. The paper begins by providing a brief overview of the geographical and historical context along with key concepts from the literature. The data is then compared and discussed based on the themes identified in the interviews.